(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research is to find out whether acceptance of online shopping as technology is based on perceived usefulness and ease of use of technology. Further, paper is exploring the role of online shopping in reducing post purchase cognitive dissonance. Statistical tools like regression analysis and t-test are applied and it is found that online shopping is reducing post purchase cognitive dissonance. Also. post purchase cognitive dissonance is significantly different in age groups, but such difference is not found between gender.